The Absence of the Verumontanum at Voiding Cystourethrography as a Sign of Prostate Maldevelopment. (2nd November 2010) - Valentini, A. L.; Ferrara, P.; Manzoni, C.; Mancini, A. P.; Pulitanò, S.; Bonomo, L.
Abstract : Prostate maldevelopment in prune-belly syndrome has only been described at necropsy. No reports are available in the "in vivo" studies. The absence of the verumontanum at voiding cystourethrography correlates with verumontanum and prostate hypoplasia. This radiographic sign can represent the earliest finding in prostate maldevelopment and might contribute to the "in vivo" assessment of the disease, especially in doubtful cases.